Acceptability of HIV pre-exposure prophylaxis in China: A systematic review and meta-analysis. (March 2022) - Yuan, Defu; Yin, Yueqi; Chen, Jianshuang; Lu, Jing; Zhou, Ying; Fu, Gengfeng; Wang, Bei
Using pre-exposure prophylaxis (PrEP) for the prevention of HIV infection is a popular, contemporary research topic. We retrieved PubMed, Web of Science, MEDLINE, Wanfang, CNKI, and Sinomed databases, and related websites to identify studies both in Chinese and English, which reported the acceptability of PrEP in China. A total of 3203 citations were retrieved, of which 54 were included. We found that the acceptability varied widely across the country, ranging from 19.1% to 94.6%, and the pooled estimate was 66.8% (95% CI: 62.0%–71.3%). Higher acceptability of PrEP was associated with the following factors: individuals with a lower educational degree, higher income, non-discriminatory attitude towards AIDS or AIDS patients, self-perceived high HIV risk, feeling that PrEP should be promoted, familiarity with PrEP, history of HIV testing, history of anal intercourse, consistent condom use, higher number of sexual partners. The main reasons for not using PrEP are doubting its validity, fear of potential side effects and financial burden, and fear of stigma for using PrEP. This review found that the acceptance in China was moderate.